To assess the impact of training about hospital infection control measures related to hemodialysis services on the knowledge of healthcare providers (HCPs) at the teaching institution of Haryana - Sukhbir Singh; Hari Kishan Aggarwal; Shekhar Pal; Hem Chandra (Journal of Family Medicine and Primary Care, 2023)
Background: Adequate knowledge among nursing professionals toward hospital infection control measures related to hemodialysis (HD) services is essential to decrease infection among patients. Objective: This study assessed nursing professionals' knowledge about hospital infection control measures related to HD services and the effect of training interventions. Settings and Designs: It was a single group, a pre–post-interventional study conducted on nursing professionals of a single apex medical college of Haryana. Materials and Methods: A pretested questionnaire consisting of two parts was used as a study tool. Statistical Analysis: Various statistical tests such as paired t-test and Pearson's correlation were used. Results: The pre-intervention group had a lower mean knowledge score (mean knowledge = 90.2786, strongly disagree [SD] = 15.52682, standard error [SE] = 1.09518) and then the post-intervention mean knowledge score (mean knowledge = 137.5622, SD = 9.72252, SE = 0.68577). Conclusions: The training program or educational intervention proved very useful for enhancing nursing professional's knowledge about hospital infection control measures related to HD services.